Development of education in Kansas - Smith, Charles F. (My University, 1902)
Introduction: Preparatory to bringing the western land into market, sections numbered 16 and 36 in each township were to be reserved for the benefit of the schools of the country. The act of 1861 admitting Kansas as a state, in addition to the above, set apart 72 sections of land in the state for the support of a state university. Educational advantages were thus early to be provided. It was the intention that all children, male and female shall have equal educational opportunities. Before schools could be provided for, however, the settlers at once began the instruction of their children at home. Out of this land appropriated to the state by the General Government has grown what is called the State Permanent School Fund which now amounts to about eight million dollars (8,000,000). This is invested in bonds of the state or counties or in those of the United States. The income from these bonds is distributed semi-annually to the proper counties of the state in proportion to the school population. This fund now amounts to about $650,000 annually. This amount divided by 650,000, an estimate of the school population of the state, gives the amount received for each pupil. Thus we see that when Kansas was admitted as a state, the Common Schools and the State University were provided for. Out of the university provision has grown the State Agricultural College and the State Normal School. These will each be taken up later in their turn. As soon as any small portion of a country becomes sufficiently settled, the attention is always turned to the establishment of a Common Public School. To meet this natural inclination the state constitution has provided for the organization of such a settlement, by the County Superintendent, into a School District.
Citation: Smith, Charles F. Development of education in Kansas. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Education; Kansas; State Agricultural College; State Normal School; State Permanent School Fund; Common Public Schools; State Colleges; Theses